A Dying Trend or a Viable Option: Dual-Role Athletic Department Employees - Brady, Lawrence; Trachsler, Tracy (Journal of Amateur Sport, 2017)
As athletic departments at the college/university level are trying to creatively balance the financial demands of supporting athletic programs with employee satisfaction and departmental needs, the topic of the dual-role employee tends to appear in conversation. The question remains, with all of the demands, in both administration and coaching, is it possible for a single person to successfully accomplish the job obligations in both areas?